1988
DOI: 10.2519/jospt.1988.9.10.345
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Isokinetic Strength in Prepubertal Males

Abstract: Twenty-nine prepubertal males P a g e = 8.2 & 1.3 years) were evaluated for concentric isokinetic strength at the knee, shoulder, and elbow joints, [at the dominant (D) and nondominant (ND) sides]. At each joint, flexion (F) was compared with extension (E) at two speeds of 30°/sec (30) versus 90°/sec (90) over each 10% of the range of motion (ROM). Reliability was estimated between identical motions at the D versus ND side. Results for X work at the knee joint indicated slightly higher work output at the ND si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Instrumented tests of muscle function yield reliable peak torque measurements in children [65,66], but the equipment is expensive and, with the exception of hand-heId dynamometers, is not transportable. Therapists serving children with arthritis in their homes or schools need inexpensive and easily administered tests that provide valid, reliable results.…”
Section: Measurement Of Muscle Functionmentioning
confidence: 99%
“…Instrumented tests of muscle function yield reliable peak torque measurements in children [65,66], but the equipment is expensive and, with the exception of hand-heId dynamometers, is not transportable. Therapists serving children with arthritis in their homes or schools need inexpensive and easily administered tests that provide valid, reliable results.…”
Section: Measurement Of Muscle Functionmentioning
confidence: 99%
“…Direct comparison of test data generated by different manufacturers' isokinetic dynamometers will help clinicians and researchers interpret promotional material, results of clinical tests, and research data. As yet, however, there have been relatively few studies that have either employed new manufacturers' machines (5, 26,[32][33][34]38,61) or directly compared isokinetic dynamometers of different manufacturers (27,62). The purpose of this study was to compare data generated by Cybex and Biodex (Shirley, NY) isokinetic dynamometers during testing of the knee joint.…”
mentioning
confidence: 99%
“…This ROM measurements of posterior shoulder tightness had high reliability and validity (ICC = 0.92, r = −0.61). The study also showed that patients with impingement syndrome had decreased shoulder internal and external rotator's strength compared to normal people, and that isokinetic measurement of internal and external rotator's strength in assessing shoulder muscle strength is a reliable way to measure strength of the rotator cuff muscle (r = 0.70) [20]. This is also supported by findings of Grossman et al [4] that posterior capsule tightness related to such a reduction of internal rotation caused the humeral head to shift toward the anterosuperior region that could lead to gradual injury of the rotator cuff [11].…”
Section: Introductionmentioning
confidence: 87%